Chromosomes of Asian cyprinid fishes: Variable karyotype patterns and evolutionary trends in the genus Osteochilus (Cyprinidae, Labeoninae, "Osteochilini") - Saenjundaeng, Pasakorn; Supiwong, Weerayuth; Sassi, Francisco M C; Bertollo, Luiz A C; Rab, Petr; Kretschmer, Rafael; Tanomtong, Alongklod; Suwannapoom, Chatmongkon; Reungsing, Montri; Cioffi, Marcelo de Bello (Genetics and molecular biology, 2020)
The Cyprinidae family is a highly diversified but demonstrably monophyletic lineage of cypriniform fishes. Among them, the genus Osteochilus contains 35 recognized valid species distributed from India, throughout Myanmar, Laos, Thailand, Malaysia, Indonesian archipelago to southern China. In this study, karyotypes and other chromosomal characteristics of five Osteochilus species occurring in Thailand, namely O. lini, O. melanopleura, O. microcephalus, O. vittatus and O. waandersii were examined using conventional and molecular cytogenetic protocols. Our results showed they possessed diploid chromosome number (2n) invariably 2n = 50, but the ratio of uni- and bi-armed chromosomes was highly variable among their karyotypes, indicating extensive chromosomal rearrangements. Only one chromosome pair bearing 5S rDNA sites occurred in most species, except O. melanopleura, where two sites were detected. In contrast, only one chromosomal pair bearing 18S rDNA sites were observed among their karyotypes, but in different positions. These cytogenetic patterns indicated that the cytogenomic divergence patterns of these Osteochilus species were largely corresponding to the inferred phylogenetic tree. Similarly, different patterns of the distributions of rDNAs and microsatellites across genomes of examined species as well as their different karyotype structures indicated significant evolutionary differentiation of Osteochilus genomes.